Work-Family Conflict in professionals in the hospital environment: analysis of predictors - De Andrade, Alexsandro Luiz (2020)
The present study investigates the predictive aspects of the work-family conflict in professionals in the hospital context. Such contexts are commonly investigated in terms of health domains and organizational factors, with effects on aspects of work-family interaction still little explored. Research on the work-family relationship is important both for organizations, for families, professionals, and society. Therefore, a survey study was conducted, with 470 workers, with a mean age of 34.50 years and an average years working in the profession of 8.0 years. Participants answered a survey composed of questions and psychological scales. The results pointed out that aspects of family interference at work were predicted by age, career time, intention to leave the organization and organizational incivility, and work to interfere in the family also involved aspects of workload, work satisfaction, organizational commitment and civility organizational structure. It is discussed suggestions for management and research on the subject in organizations.